Membandingkan Pengeluaran dan Preferensi Tanaman Obat dan Obat Kimia di Masyarakat Sekitar Hutan Wilayah Kerja Kesatuan Pengelolaan Hutan Kulawi - ladiva, ladiva; Umar, Syukur; Pribadi, Hendra; Maiwa, Arman; Hulu, Amati Eltriman; Lareke, Amir (Savana Cendana, 2024)
This study investigated the expenditure patterns and preferences regarding medicinal plants and chemical drugs in communities living around the forest of the Kulawi Forest Management Unit working area. The purpose of this study was to identify the types of medicinal plants used by the community, as well as to compare the expenditure of medicinal plants with chemical drugs. The sampling technique used was Stratified Random Sampling (SRS). The sampling method involved 90 respondents who were sampled in this study. Data analysis used Comparative analysis of paired-Samples T test. The results of the study showed that there are 27 species and 20 families of medicinal plants in the Kulawi Forest Management Unit Working Area that are utilized by the community. These continue to be a major health resource in the region, as evidenced by 70% of the community expressing preference and utilization of these plants over chemical drugs. Notably, expenditure on chemical drugs is only 30% of total health care costs. These findings indicate an increasing recognition within the community of the advantages associated with traditional medicine, It is imperative to maintain the efficacy of herbal medicine to achieve sustainable healthcare in the region. The results of the Paired SampleTest showed that the significant value of the expenditure of medicinal plants and chemical drugs was .000, which means the value is smaller than 0.05. This means that the comparison of expenditure on medicinal plants and chemical drugs is not the same. There is a significant comparison of expenditure on the use of medicinal plants with chemical drugs in the community of the Kulawi Forest Management Unit working area, which occurs due to increased public awareness of the benefits of natural medicinal plants and is affordable or more accessible for some people.